Exploitation of Solar Energy between the German Leadership and the Reality of the Algerian Experience: Analytical Study During the Period (2000-2017) (International Journal of Sustainable Energy and Environmental Research, 2020)
This study aims to reveal the reality of the Algerian experience in the exploitation of solar energy, considering that Algeria is a large country in terms of space and climate capabilities that allow it to attract this kind of renewable energies. The study also observes the German experience in this field in order to benefit from it; thus, it relied upon the analytical descriptive approach. The results of the study showed the limited exploitation of this type of energy in Algeria. Despite the gradual improvement in the use of solar energy, mainly since 2015, this improvement is not as expected as it recorded an output of 244.1 MW in 2016, and the output did not exceed 400 MW until the end of 2017. This is despite the tendency of Algeria in activating and assimilating solar energy and developing its exploitation as an alternative energy for fossil energy, which comes as a priority within the National Renewable Energy Program 2015-2030. The results of the study also showed the high level achieved by Germany in the exploitation of solar energy despite the obstacles encountered where the country is cloudy. Germany’s solar power capacity reached 40988 MW in 2016 after it was within 114 MW in 2000. This would not have been achieved in Germany in the absence of the promotion of investment in renewable solar energy and consumption, where the growth rate of solar energy consumption reached about 9% in 2016, but in Algeria remains very modest, as less than 0.05%.